2016
DOI: 10.3390/rs8030245
|View full text |Cite
|
Sign up to set email alerts
|

Potential of High Spatial and Temporal Ocean Color Satellite Data to Study the Dynamics of Suspended Particles in a Micro-Tidal River Plume

Abstract: Ocean color satellite sensors are powerful tools to study and monitor the dynamics of suspended particulate matter (SPM) discharged by rivers in coastal waters. In this study, we test the capabilities of Landsat-8/Operational Land Imager (OLI), AQUA&TERRA/Moderate Resolution Imaging Spectroradiometer (MODIS) and MSG-3/Spinning Enhanced Visible and Infrared Imager (SEVIRI) sensors in terms of spectral, spatial and temporal resolutions to (i) estimate the seawater reflectance signal and then SPM concentrations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 49 publications
(104 reference statements)
3
51
0
1
Order By: Relevance
“…Among many atmospheric correction algorithms available for data processing in SeaDAS we considered two, the standard atmospheric correction method for MODIS high resolution data SWIR [69], and the MUMM [70] atmospheric correction method, because previous studies [56,[70][71][72] have demonstrated that these two atmospheric correction algorithms are effective for turbid coastal waters. The SWIR atmospheric algorithm estimates the aerosol reflectance using the 1240 nm and 2130 nm MODIS bands while the MUMM atmospheric correction is based on the spatial homogeneity of water-leaving radiances and aerosol ratios for the MODIS 748 nm and 869 nm bands [71].…”
Section: Atmospheric Correctionmentioning
confidence: 99%
“…Among many atmospheric correction algorithms available for data processing in SeaDAS we considered two, the standard atmospheric correction method for MODIS high resolution data SWIR [69], and the MUMM [70] atmospheric correction method, because previous studies [56,[70][71][72] have demonstrated that these two atmospheric correction algorithms are effective for turbid coastal waters. The SWIR atmospheric algorithm estimates the aerosol reflectance using the 1240 nm and 2130 nm MODIS bands while the MUMM atmospheric correction is based on the spatial homogeneity of water-leaving radiances and aerosol ratios for the MODIS 748 nm and 869 nm bands [71].…”
Section: Atmospheric Correctionmentioning
confidence: 99%
“…Field measurements used for the calibration of SPM models and multi-conditional algorithm were carried out during four bio-optical cruises (from April 2012 to July 2014) in the two selected test At each station, hyperspectral reflectance measurements were carried out using TriOS-RAMSES radiometers in the same way as the methodology described in [13]. The protocol described in [44] based on the NASA (National Aeronautics and Space Administration) protocols [45] to compute the remote sensing reflectance (R rs , sr −1 ).…”
Section: In Situ Spm and Reflectance Datamentioning
confidence: 99%
“…The RSR curves in the visible and NIR bands are shown as dashed lines in Figure 2. Although L8/OLI is not designed for ocean monitoring, its advantages of high spatial resolution and the increased number of bands, combined with its improved signal-tonoise ratio and data quality, make it increasingly used in ocean color remote sensing research and especially in estuarine and coastal research [26][27][28][29][30][31][32][33].…”
Section: Satellite Imagesmentioning
confidence: 99%